Supercapacitor and supercapattery as emerging electrochemical energy stores - Chen, George Z. (Taylor and Francis, 2016)
This article reviews critically selected recent literature on electrochemical energy storage (EES) technologies, focusing on supercapacitor and also supercapattery which is a generic term for various hybrid devices combining the merits of rechargeable battery and supercapacitor. Fundamentals of EES are explained, aiming at clarification of some literature confusions such as the differences between capacitive and non-capacitive Faradaic charge storage mechanisms, and between cathode and positive electrode (positrode), and between anode and negative electrode (negatrode). In particular, the concept and origin of pseudocapacitance are qualitatively correlated with the band model for semiconductors. Strategies for design and construction of supercapattery are discussed in terms of both the materials structures and device engineering. Selection of materials, including electrolytes, is another topic reviewed selectively. Graphenes and carbon nanotubes are the favourable choice to composite with both capacitive and non-capacitive redox materials for improved kinetics of charge storage processes and charge-discharge cycling stability. Organoaqueous electrolytes show a great potential to enable EES to work at sub-zero temperatures, whilst solid ion conducting membranes and ionic liquids can help develop high voltage (> 4.0 V) and hence high energy supercapatteries.